Answer:
The final velocity of the first glider is 3.39553 m/s in the opposite direction
The final velocity of the second glider is 0.31553 m/s in the same direction
Step-by-step explanation:
= Mass of first glider = 0.14 kg
= Mass of second glider = 0.299 kg
= Initial Velocity of first glider = 0.8 m/s
= Initial Velocity of second glider = -2.28 m/s
= Final Velocity of first glider
= Final Velocity of second glider
As momentum and Energy is conserved
![m_(1)u_(1)+m_(2)u_(2)=m_(1)v_(1)+m_(2)v_(2)](https://img.qammunity.org/2020/formulas/physics/college/z0dguiut5nco4e93k0bgl2gd7k28sarnzi.png)
![{\tfrac {1}{2}}m_(1)u_(1)^(2)+{\tfrac {1}{2}}m_(2)u_(2)^(2)={\tfrac {1}{2}}m_(1)v_(1)^(2)+{\tfrac {1}{2}}m_(2)v_(2)^(2)](https://img.qammunity.org/2020/formulas/physics/high-school/lblrhrmv2g9rb96xsg4033rbl4aghp5vku.png)
From the two equations we get
![v_(1)=(m_1-m_2)/(m_1+m_2)u_(1)+(2m_2)/(m_1+m_2)u_2\\\Rightarrow v_1=(0.14-0.299)/(0.14+0.299)* 0.8+(2* 0.299)/(0.14+0.299)* -2.28\\\Rightarrow v_1=-3.39553\ m/s](https://img.qammunity.org/2020/formulas/physics/high-school/jogsrvxl6ixxvthz6vh03qtnctavfkraif.png)
The final velocity of the first glider is 3.39553 m/s in the opposite direction
![v_(2)=(2m_1)/(m_1+m_2)u_(1)+(m_2-m_1)/(m_1+m_2)u_2\\\Rightarrow v_2=(2* 0.14)/(0.14+0.299)* 0.8+(0.299-0.14)/(0.14+0.299)* -2.28\\\Rightarrow v_2=-0.31553\ m/s](https://img.qammunity.org/2020/formulas/physics/high-school/wwc7mgpyellbv9hh29e0jsdqrkpeyj8ayc.png)
The final velocity of the second glider is 0.31553 m/s in the same direction